Analyzing Expert Criteria for Authentic Resident Communication Skills. Issue 1 (20th January 2022) - Han, Heeyoung; Hingle, Susan Thompson; Koschmann, Timothy; Papireddy, Muralidhar Reddy; Ferguson, Jacqueline
Abstract: Phenomenon : Training and assessing communication skills requires flexible and holistic approaches, including feedback practices. Historically, assessing communication skills has predominantly relied on itemized scoring, which is less useful for providing meaningful feedback to learners. Even more troublesome, theoretical scoring criteria tend to become a refractive lens allowing observation of only the conduct that aligns with the theory. Few skills assessment efforts have embraced a holistic understanding of how physician-patient communication skills are enacted in real patient care. Therefore, this study focused on what experts refer to when they speak about physicians' communication skills and what they treat as important when evaluating these skills enacted during real patient encounters. Approach : This qualitative study was based on observations and grounded theory. Residents' encounters with real patients were recorded as part of a formative communication skills assessment program from July 2015 to June 2016. Evaluation panels with diverse backgrounds (e.g., medicine, education, communication, conversation analysis, and layperson) listened to these recordings and jointly developed feedback comments for the resident from January 2016 to July 2017. For this study, we recorded forty-one panel discussions to observe their consensus evaluation. We conducted open and axial coding using a constant comparison approach to generate themes from the data. Findings : Elements of communication skills were connected and interdependent around the concepts of thoroughness and natural flow, which were not addressed by formative assessment criteria. Themes included (1) thoroughness within a boundary via agenda-setting; (2) natural yet, controlled flow: authentic conversation by active listening and questioning; (3) making agenda setting explicit to all parties in the beginning; (4) designing questions using both open-ended and closed questions; (5) pre-/post-conditions for patient education: patient contextual factors and teach-back; (6) preconditions for shared decision-making: patient education and patient contextual factors; and (7) multifaceted empathy demonstrated in multiple ways. Insights : The main message of the study findings is that communication skills criteria should be treated as organically interrelated and connected in assessing physicians' communication skills. Current communication skills assessment practice should be revisited as it itemizes physicians' communication skills as distinct and separate constructs rather than mutually affecting dynamics. Rather than imposing a theoretical rubric, assessment criteria should evolve through naturalistic observations of physician-patient communication.